Analysis on Vegetation for Landscape Arragement of Agrotourism in Cikapek Leuwidamar Lebak District - Wijanarko, Puji; Wakyudi; Alicia, Velma (Institut Teknologi dan Bisnis Ahmad Dahlan, 2025)
Vegetation analysis is important for regulating the balance of carbon dioxide and oxygen in the air, improving the physical, chemical, and biological properties of the soil, and managing groundwater. The aim is to determine the composition and structure of the plants present and located in the Cikapek Agrotourism area, Lebakparahiang Village, Leuwidamar District, Lebak Regency. The method used is sample plots measuring 100 m x 100 m (1 Ha) with 3 (three) observation plots, along the trail line there are plots at equal intervals. The plot sizes are (a) 5 m × 5 m for the sapling phase, (b) 20 m × 20 m for the tree phase. The observed tree growth phases: a. Mature trees with a diameter ≥ 20 CM b. Saplings, young trees with a height ≥ 1.5 M. Results indicate the plant species Cocos nucifera or coconut tree has the highest IVI (Important Value Index) of 0.92651% and the lowest Importance Value Index is the sugar palm plant with an IVI of 0.583%, and the lowest Important Value Index is the Waru plant with an IVI of 0.112%. However, the research should address broader regional planning concerns, integrating other biophysical factors to ensure a comprehensive and harmonious development strategy. This will help create an agrotourism area that supports ecological balance, aligns with the needs of the local community, and promotes long-term environmental sustainability.